Analysis of Pax-Ottomanica in Minorities Society : A Case Study of Millet System - Cut Meurah Rahman; Ida Fitriana (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2021)
This paper focuses on Pax-Ottomanica in a case study of the Millet System through multi ethnic and multi religious communities in the Ottoman Empire. In particular, the Millet System has successfully roamed people in Europe, Asia, and Africa for nearly 600 years. This paper also discusses Islamic law on the relationship between other religions such as Judaism and Christianity. This study uses a qualitative method with a whole literature approach. Based on the data analyzed, it was found that harmony occurs between fellow religious and ethnic people with the freedom to embrace their respective religions and maintain their respective cultures. This paper aims to analyze the state of the multi-ethnic and multi-religious society in the Ottoman Empire by providing various references from both Turkish and Western historians. In addition, this paper aims to introduce Ottoman-style freedom through this Millet system, which has succeeded in bringing all non-Muslim communities into one Ottoman commonwealth.